Performance Enhancement of Photovoltaic Panels Using Passive Heatsink Cooling and Single-axis Solar Tracking - Apribowo, Chico Hermanu Brillianto; Winda, Wiwik Nur; Maghfiroh, Hari; Iftadi, Irwan; Baballe, Muhammad Ahmad (Universitas Ahmad Dahlan, 2025)
Indonesia's persistent tropical climate and strong sunlight year-round lend themselves well to photovoltaic (PV) applications. However, prolonged sun exposure raises panel temperatures and reduces energy conversion efficiency. This study examines how to experimentally enhance the power output and efficiency of PV systems by combining single-axis solar tracking with passive heatsink cooling. On sunny days, two identical 50 W polycrystalline PV panels were evaluated in Surakarta, Indonesia. Four setups were tested: baseline (no tracking or cooling), tracking only, cooling only, and a combination of both. Temperature, voltage, and current data were gathered using calibrated INA219 and MLX90614 sensors. Results indicate the system can enhance efficiency and power output. Tracking alone improved power by 26.42% and efficiency by 2.16%; cooling using an aluminum heatsink boosted power by 40.28% and efficiency by 3.39%. Combining tracking and cooling yielded the highest power increase of 55.61%, with a 2.79% efficiency gain. These findings demonstrate the reduced efficiency benefits due to thermal effects despite higher irradiance in tracking systems. This research offers practical insights for optimizing PV performance in tropical regions and supports developing cost-effective, hybrid enhancement strategies.